Pisang Nangka (Musa paradisiaca) As An Alternative Media For Aspergillus niger Growth - Firdha Rachmawati; Budiman; Sisna Imalda; Lilis Puspa Friliansari (Indonesian Journal of Science and Education, 2023)
Nangka banana (Musa paradisiaca) is one of the most popular bananas in Indonesia. Therefore, the production of waste will increase along with the use of bananas. Nangka banana peel and flesh can be used as an alternative media for mushroom growth because of its high carbohydrate content. The purpose of this study was to observe the growth of Aspergillus niger on alternative media made from nangka banana with concentrations of 8%, 9%, 10%, 11% and 12% and to determine the optimum variation and concentration of alernative media. Aspergillus niger was grown on nangka banana flesh media, nangka banana peel media and mix of nangka banana peel and flesh as well as PDA (Potato Dextrose Agar) media as a positive control using the single dot method. Colony diameter and pigmentation were observed for five days. The variation of nangka banana mix media with a concentration of 12% is the optimum variation and concentration to grow Aspergillus niger. Keywords: Alternative media, Aspergillus niger, nangka banana